Effect of arbuscular-mycorrhizal inoculation in low phosphorus soil in relation to P-utilization efficiency of wheat (Triticum aestivum) genotypes - PANDEY, RENU; SINGH, BHUPINDER; NAIR, T V R (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted in pots containing field soil low in available P (7.8 mg P/kg soil) to evaluate the response of wheat (Triticunl aestivunz L. emend. Fiori & Paol.) genotypes to inoculation with arbuscular-mycorrhiza (AM) and its effect on phosphorus-utilization efficiency (PUE). The genotypes were inoculated with or without arbuscular-mycorrhiza fungi (Gio1nus macrocarpUln Tul & Tul) in the absence ofP application to soil. Significant increase was observed in per cent root colonization (up to 50%), shoot (18-88%), root (25-960/0) and whole plant dry matter (29-91°1’0) under +AM inoculation, whereas the shootroot ratio was high under -AM. Phosphorus uptake in shoot was significantly higher due to +AM treatment in ’DL 1010-5’ (39%) and ’DL 2044-1’ (60%). Similarly, genotypes also showed a wide range of response to +AM under P stress. Genotype ’DLIOIO-5’ recorded highest (191%) degree of dependency on mycorrhiza and also produced nlaximunl number oftillers (5.67), shoot biornass (4.68 glplant), total plant dry matter (6.52 g/plant) and had high amount ofP uptake (10.17 mg/plant). The genotypes exhibiting a positive response to +AM such as more number of tillers, increased dry matter, higher root colonization, increased uptake of nutrients and higher efficiency ofP utilization under P stress would provide the breeders with gene pool to develop genotypes with efficient P uptake and utilization abilities.